2020
DOI: 10.1016/j.lungcan.2019.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to “Evaluation of a health service adopting proactive approach to reduce high risk of lung cancer: The Liverpool Healthy Lung Programme” [Lung Cancer 134 (August) (2019) 66–71]

Abstract: The publisher regrets the author Darcy Fidoe was incorrectly spelt as Darcy Fideo.The publisher would like to apologise for any inconvenience caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the UK, a number of pilots have shown promising results in terms of participation rates of 40 to 50%, good early stage detection rates, and low rates of harm, especially in those eventually shown not to have cancer. 29,38,42,62 Screening programmes require robust local and national quality assurance systems underpinned by agreed protocols and standards, such as those available in the USA 16,17 and UK. 18,19 These cover all aspects of screening including administration, the screening process and evaluation as well as defining the responsibilities of individuals running the programme.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…In the UK, a number of pilots have shown promising results in terms of participation rates of 40 to 50%, good early stage detection rates, and low rates of harm, especially in those eventually shown not to have cancer. 29,38,42,62 Screening programmes require robust local and national quality assurance systems underpinned by agreed protocols and standards, such as those available in the USA 16,17 and UK. 18,19 These cover all aspects of screening including administration, the screening process and evaluation as well as defining the responsibilities of individuals running the programme.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“… 12 The Liverpool Healthy Lung Programme found that a community-based proactive approach was effective in reaching and screening for LC in deprived areas. 13 However, very few of these studies were pragmatic RCTs.…”
Section: Introductionmentioning
confidence: 99%